Fatores de risco para a saúde de funcionários de uma instituição pública de ensino superior - Carvalho, Conceição de Maria Moita Machado de (2012)
Background: Coronary artery diseases (CAD) are the biggest killers in the world and in Brazil, representing a major public health problem and major socioeconomic impact. Objective: To identify risk factors (RF) earnings and the health conditions of public servants. Methods: Cross-sectional study involving 68 servers between men and women, mean age 54 ± 6 years, university officials and federal Mato Grosso included in the program CARDIO UFMT. Inclusion criteria: age> 35 years, hypertension, diabetic, overweight and / or dyslipidemia. Were performed lipid profile, blood glucose and exercise testing, echocardiography and carotid ultrasonography. After the volunteers were divided into three groups according to the amount of accumulated FR: G1 = 3; G2 = 4, G3 = 5 or more RF. He was made the Kruskal-Wallis test (nonparametric ANOVA) with p ≤ 0.05. Results: The sample was distributed in G1 = 28% = 30% G2, and G3 = 42%. The TAG (0.0250), HDL (0.0007), GLI (0.0018), BMI (0.0001) and Framingham score changed significantly between the groups with and worse accumulation of FR. When the sample was divided by sex significant differences were found for age (0.0001), weight (0.0001), BMI (0.0343), HDL (0.0001), GLI (0.0001), VO2 (0.0001), FE (0.0001), LVM (0.0001) and VPS (0.0001). Conclusion: Although both sexes are capable of important cardiovascular risk men were more affected by this condition. The accumulation of FR significantly worsens the clinical picture of these patients, which may result in worsening of the overall condition of health, higher rates of absenteeism, disability in activities of daily living and retire early.